If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -4 = y Combine like terms: 5 + -4 = 1 1 = y Solving 1 = y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 1 + -1y = y + -1y Combine like terms: y + -1y = 0 1 + -1y = 0 Add '-1' to each side of the equation. 1 + -1 + -1y = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1y = 0 + -1 -1y = 0 + -1 Combine like terms: 0 + -1 = -1 -1y = -1 Divide each side by '-1'. y = 1 Simplifying y = 1
| a-3=12 | | x^2+30x+30=0 | | 6y+20+7x=180 | | 9x=4x+40 | | 10x=8x+12 | | y=10x-37 | | 2x^2+9y=225 | | 5x+10=4x+11 | | 2(x+3)-1=11 | | 8x-10+7x=180 | | 3.14*b-b^2=2.25 | | x*300=4700 | | -(-1)+2=y | | -5=y/6 | | b-b^2=2.25 | | 5x+1.5-3.1x=0.7x-3.9 | | 3x+29y=5 | | 13x*67=5x+8x*4 | | (1-x)*5.2+x*3.6=70.57 | | 9x+11-2x=13-14x-15 | | 9z+3-7z=30-7z | | (7x+8)(8x-9)=0 | | -3(x+2)+4=5(x+5)+6 | | .5x-2= | | 27=48 | | 5(x-2)+3(2x+1)=26 | | -1-3=y | | 2x-35=6x+2 | | 2x+2-4=2/3 | | 15x+45=30 | | (2x-3)(2x+3)=135 | | -27+4x=7x+48 |